Solid Bath Soap Formulation with Butterfly Pea Flower Extract (Clitoria ternatea) and Virgin Coconut Oil (VCO) - Rejeki, Dwi Putri; Fitriani; Mardiana, Rosa (Open Global Scientific Journal, 2025)
Background: Solid bath soap is a widely used cleansing product that must meet quality and skin safety requirements. The use of synthetic ingredients in commercial soaps has the potential to cause irritation, so developing natural soaps is a safer alternative. Butterfly pea flowers (Clitoria ternatea L.) are known to contain active compounds such as flavonoids, saponins, and tannins, which have antibacterial and antioxidant properties. Virgin coconut oil (VCO) serves as a good base for vegetable fat in the saponification process.Aims: This study aims to formulate a solid bath soap made from VCO with the addition of ethanol extract of butterfly pea flowers and to evaluate its physical characteristics and safety.Methods: The research was conducted experimentally using a maceration method using 96% ethanol to obtain butterfly pea flower extract. Solid soap was formulated in four formulas: one control formula without extract (F0) and three formulas with varying concentrations of butterfly pea flower extract (F1, F2, and F3). Evaluation of the preparations included organoleptic tests, homogeneity, pH, skin irritation tests, and preference tests.Results: The results showed that all soap formulas were solid, homogeneous, and organoleptically stable. The pH values ​​of formulas F1, F2, and F3 were within the soap pH range required by the Indonesian National Standard (SNI), while F0 did not meet the pH criteria for solid soap. Irritation tests showed that all formulas were safe and did not cause irritation in volunteers. Based on the preference test, formulas with low to medium extract concentrations were preferred by respondents.Conclusion/ Recommendation: Therefore, butterfly pea flower extract and VCO have the potential to be used as natural ingredients in safe and high-quality solid soap formulations.